MANDATORY ELEMENTS OF THE CRIME OF HUMAN TRAFFICKING ACCORDING TO THE CRIMINAL CODE OF GEORGIA - Tsikarishvili, Kakha (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the aim of this paper is to analyze mandatory elements of the crime of human trafficking according to the criminal code of Georgia. Methods: mandatory elements of human trafficking shall be analyzed in accordance with the structure of corpus delicti. According to dominating legal theory in Georgia the corpus delicti (first element of the crime) is composed of objective and subjective elements: while the conduct, result and means of the commission of the crime are included in objective elements, the purpose and intent of the crime are part of the subjective elements. Results: it appears that the crime of human trafficking is made of 5 basic elements: Sale and purchase (or other illegal transaction); Recruitment; Coercion (or deception); Limitation of freedom/control of the victim; Exploitation. However, none of these elements are mandatory for the crime of human trafficking. They are optional in nature. Also, it appears that the Georgian law on human trafficking is too wide and requires modification, because on the one hand it may not entirely fit with international legal definition of human trafficking and on the other hand may overlap with other crimes already covered by Georgian criminal code. Discussion: the Georgian criminal code adopted in 1999 did not contain the crime of human trafficking. In 2003, the crime of human trafficking was included in the chapter of crimes directed against human rights and freedoms (Chapter 23). This chapter contains three articles related to the crime of human trafficking: Article 1431 (Human Trafficking) Article 1432 (trafficking of minors) and Article 1431 (benefiting from the services of the victims of human trafficking); For proposer qualification of the crime of human trafficking, it is important to identify its elements and find out whether these elements are mandatory or optional. While the crime of human trafficking has a complex composition, many terms applied by the law cause divergent interpretations in legal theory. However, its important that the terms are interpreted in accordance with the international agreements on human trafficking to which Georgia is a party.